Явище розрідження у грунтах та фактори, що на нього впливають - Кріль, Т.В. (Інститут геологічних наук НАН України, 2009)
Водонасыщенные дисперсные грунты даже при незначительных динамических действиях могут разжижаться. При этом массив грунта может полностью терять устойчивость и приобретать свойства вязкой жидкости. Исследовано и подробно разъяснено физику явлений разрежения водонасыщенных грунтов. Установлены основные критерии оценки устойчивости. Приведены факторы, которые влияют на способность грунтов разжижаться. Saturated dispersible soils even at insignificant dynamic actions can be diluted. Thus the array of soil can fully lose stability and acquire properties of viscous liquid. It is investigational and physics of the phenomena of rarefaction of the saturated soils is explained in detail. The basic criteria of estimation of stability are set. Factors which influence on ability of soils to be diluted are resulted.